2018
DOI: 10.1111/jcmm.14014
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia alters the effects of cardiomyocyte‐derived extracellular vesicles on macrophage activation

Abstract: Myocardial ischaemia is associated with an exacerbated inflammatory response, as well as with a deregulation of intercellular communication systems. Macrophages have been implicated in the maintenance of heart homeostasis and in the progression and resolution of the ischaemic injury. Nevertheless, the mechanisms underlying the crosstalk between cardiomyocytes and macrophages remain largely underexplored. Extracellular vesicles (EVs) have emerged as key players of cell‐cell communication in cardiac health and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…Because the molecular signature of circulating EVs may represent an important biomarker of ischemic disease, reflecting alterations within the injured myocardium, we started by isolating serum EVs from a mouse model of I/R injury. In agreement with our previous observations, isolated circulating EVs were positive for the tetraspanins CD63 and CD9, presented typical morphology and EV size and their secretion was up-regulated in animals subjected to I/R ( Fig 1A-C) (Deddens et al, 2016;Paiva et al, 2019). Interestingly, the vesicle extract was positive for the specific cardiomyocyte marker Troponin T, suggesting that at least part of these EVs were from cardiac origin (Fig 1A).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Because the molecular signature of circulating EVs may represent an important biomarker of ischemic disease, reflecting alterations within the injured myocardium, we started by isolating serum EVs from a mouse model of I/R injury. In agreement with our previous observations, isolated circulating EVs were positive for the tetraspanins CD63 and CD9, presented typical morphology and EV size and their secretion was up-regulated in animals subjected to I/R ( Fig 1A-C) (Deddens et al, 2016;Paiva et al, 2019). Interestingly, the vesicle extract was positive for the specific cardiomyocyte marker Troponin T, suggesting that at least part of these EVs were from cardiac origin (Fig 1A).…”
Section: Resultssupporting
confidence: 92%
“…For example, EVs secreted by cardiomyocyte progenitor cells, mesenchymal stem cells, glucosedeprived H9c2 cardiomyoblasts, and ischemic cardiomyocytes induce endothelial cell proliferation and angiogenesis (Garcia et al, 2015;Vrijsen et al, 2016;Ribeiro-Rodrigues et al, 2017a). Moreover, cardiomyocyte-derived EVs can induce gene expression changes in fibroblasts or activate macrophages (Bang et al, 2014;Paiva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Groundbreaking studies unveiled the presence of Cx43 in EVs, in which Cx43 channels facilitate the release of vesicle content into recipient cells [128,129]. Moreover, several studies have demonstrated that the content of EVs secreted by cardiomyocytes is affected by ischemia [130,131]. Although the impact of ischemia on the sorting of Cx43 into EVs has never been addressed, it is conceivable that an interplay between EV biogenesis and autophagic degradation determines the final fate of Cx43 in ischemic cardiomyocytes.…”
Section: Cx43 Protein Partners and Their Role In Cardiac I/r Injury-mmentioning
confidence: 99%
“…Apart from such interactions, cardiomyocytes can also more directly instruct macrophage polarization and activities. Thus, extracellular vesicles isolated from mouse neonatal cardiomyocytes, when applied on macrophages induce p38MAPK activation and inflammatory gene expression (197). Moreover, early after MI, cardiomyocytes transiently overexpress and release several Reg3 proteins, members of the C-type lectin family (142).…”
Section: Cardiomyocyte-cardiac Fibroblast-macrophage Interactionsmentioning
confidence: 99%
“…Local administration of Reg3 protein paralogues in mice promoted recruitment of pro-inflammatory macrophage subsets (MHC-II hi /Ly6C lo and MHC-II lo /Ly6C lo ), whereas the pro-angiogenic and reparative Ly6C hi subpopulation was suppressed. Moreover, under ischemic conditions, cardiomyocytes seem to induce via secreted vesicles the adhesion of macrophages to ECM and lead to the reduction of their ability to phagocytose, suggesting a paracrine cardiomyocyte-macrophage crosstalk (197) that impairs debris clearance in MI. The debridement of damaged cardiac tissue is an important parameter, as its impairment by depletion of macrophages following cryo-injury in the mouse leads to diminished myofibroblast infiltration and vascularization and a thinner free wall accompanied by increased dilatation and mortality rate (198).…”
Section: Cardiomyocyte-cardiac Fibroblast-macrophage Interactionsmentioning
confidence: 99%